COVID-19 High Frequency Phone Surveys in Latin America : Technical Note on Sampling Design, Weighting, and Estimation - Flores Cruz, Ramiro (World Bank, Washington, DC, 2021)
The Coronavirus disease 2019 (COVID-19) high-frequency phone survey (HFPS) 2020 was conducted in 13 Latin American countries: Argentina, Bolivia, Chile, Colombia, Costa Rica, Dominican Republic, Ecuador, El Salvador, Guatemala, Honduras, Mexico, Paraguay, and Peru. It followed a panel sample over three waves of data collection in 12 countries and over four waves in Ecuador. All waves spanned from May to August 2020 and each wave’s collection period lasted about ten days on average. The survey was administered to one adult per household. Each respondent was presented with both individual and household-level questions. All national samples were based on a dual frame of cell and landline phones, and selected as a one-stage probability sample, with geographic stratification of landline numbers. The samples were generated through a random digit dialing (RDD) process covering all cell and landline telephone numbers active at the time of the sample selection. Survey estimates represent households with a landline or at least one cell phone and individuals of 18 years of age or above who have an active cell phone number or a landline at home.